2019
DOI: 10.1007/s11205-019-02075-2
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping Public Concerns About Class Immobility in China

Abstract: Public concerns about class immobility represent awareness of social closure and economic inequality on the part of members of the public. We provide the first representative portrait and empirical analysis of the growing immobility concerns among the Chinese. Using online query volume data from Baidu, the most widely used search engine in China, we extract the overall index of searching immobility-related words to measure the provincial level of concerns about immobility. We found that concerns about immobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 97 publications
2
11
0
Order By: Relevance
“…1 It clearly indicates that concern about inequality and mobility began to increase in 2009. The trend shown in Figure 1 is consistent with Li et al’s (2019) research. The above findings, together, suggest an across-the-board increase in criticality of inequality after 2009 and support the following hypotheses:…”
Section: The Subjective Dimension Of Inequality and Its Political Effectssupporting
confidence: 90%
See 3 more Smart Citations
“…1 It clearly indicates that concern about inequality and mobility began to increase in 2009. The trend shown in Figure 1 is consistent with Li et al’s (2019) research. The above findings, together, suggest an across-the-board increase in criticality of inequality after 2009 and support the following hypotheses:…”
Section: The Subjective Dimension Of Inequality and Its Political Effectssupporting
confidence: 90%
“…The first main covariate is the survey wave, a categorical variable. I use the 2009 wave as the reference category as recent research suggests that concerns about inequality and mobility rose only after 2009 (Li et al 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some studies have shown that class background continues to play a key role in people’s access to education and advances in their professional status [ 32 ]. This factor has become more important, as class immobility in China has been shown to have increased from 1996 to 2012 [ 33 ] and to be profoundly influenced by social structural factors, such as regional political and socioeconomic conditions [ 34 ]. Given this situation, income inequality may no longer be a positive signal of hope and an expectation of upward mobility, especially in the context of reinforced class solidification.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%